2008
DOI: 10.1108/13527590810912322
|View full text |Cite
|
Sign up to set email alerts
|

Top management team and corporate performance: a study of Greek firms

Abstract: PurposeThis paper seeks to explore the role that boards can play in the contribution of organizational performance and to empirically examine the relationship between the chairman, key board composition variables and firm performance.Design/methodology/approachThe data presented are drawn from a sample of 27 chairmen of Greek corporations listed in the Athens Stock Exchange (ASE). The authors examine hypothesized links between the demographic characteristics of the chairmen of the board, board composition vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 50 publications
0
26
0
10
Order By: Relevance
“…There are generally only a few studies that investigated the association between CEO tenure and firm performance in the developed countries and reported a positive association (Koufopoulos et al, 2008;Simsek, 2007). Some other studies revealed reported similar results with the developing countries like , Herly and Sisnuhadi (2011) and Kyereboah-Coleman (2007).…”
Section: Ceo Tenure and Firm Performancementioning
confidence: 54%
“…There are generally only a few studies that investigated the association between CEO tenure and firm performance in the developed countries and reported a positive association (Koufopoulos et al, 2008;Simsek, 2007). Some other studies revealed reported similar results with the developing countries like , Herly and Sisnuhadi (2011) and Kyereboah-Coleman (2007).…”
Section: Ceo Tenure and Firm Performancementioning
confidence: 54%
“…By contrast, more recently, other scholars (e.g. Koufopoulos et al, 2008) have found that the higher mean age of directors provides no guarantee of contributing to greater effectiveness.…”
Section: H6 Soes Whose Boards Have a Larger Proportion Of Members Wimentioning
confidence: 83%
“…Many scholars have pointed out that social capital allows for changes in operational performance by facilitating competitive advantage and sustainability (Kale, Singh & Perlmutter, 2000;Doz, 1996). From the perspective of management, organizational performance is highly related to profitability (Koufopoulos, Zoumbos, Argyropoulou & Motwani, 2008).…”
Section: Introductionmentioning
confidence: 99%